Costa Rica : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This Selected Issues paper examines recent economic developments and economic growth in Costa Rica. The paper highlights that real GDP growth of Costa Rica slowed to 1.7 percent, from more than 8 percent a year in 1998-99, reflecting in part deterioration in the terms of trade, the end of the construction phase of a large foreign direct investment project by Intel, and the effect of high real interest rates on domestic demand. The paper also provides a brief overview of some methodological difficulties usually encountered in calculating a country's real effective exchange rate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet